2015
DOI: 10.1089/jmf.2014.3408
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Attenuates Hepatic Inflammation in Chronic Alcohol-Fed Rats Through Inhibition of TLR4/MyD88 Signaling

Abstract: Accumulating evidence indicates that overconsumption of ethanol contributes in many ways to the pathogenesis of hepatic injury. Although studies indicate that taurine decreases lipogenesis, oxidative stress, and inflammatory cytokines, the protective effect of taurine against alcohol-induced liver injury is still unclear. To clarify the precise signaling involved in the beneficial effect of taurine on alcohol-induced liver injury, rats were randomly divided into four treatment groups: (1) control (Ctl), (2) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Importantly, the ROS level was related to the action of GSH-PX. These data are consistent with previous reports that taurine ameliorated the elevated iNOS and ROS caused by bacterial infection in rats and mammary epithelial cells [30][31][32]. Thus, that low concentration of taurine leads to the increased survival of zebrafish infected with V. alginolyticus is partly attributed to adjustments to inflammation-related innate immunity, NO, and ROS levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, the ROS level was related to the action of GSH-PX. These data are consistent with previous reports that taurine ameliorated the elevated iNOS and ROS caused by bacterial infection in rats and mammary epithelial cells [30][31][32]. Thus, that low concentration of taurine leads to the increased survival of zebrafish infected with V. alginolyticus is partly attributed to adjustments to inflammation-related innate immunity, NO, and ROS levels.…”
Section: Discussionsupporting
confidence: 93%
“…Reports indicate that taurine attenuates inflammation via decreasing inducible nitric oxide synthase (iNOS) and ROS in rats and mammary epithelial cells [30][31][32]. Thus, we investigated the effect of malate and taurine on nitric oxide (NO) and ROS production in fish.…”
Section: Malate and Taurine Influence Inducible Nitric Oxide Synthasementioning
confidence: 98%
“…BCAA supplementation clinically showed an anti‐fatigue ability during exercise due to an enhancement of fatty acid β‐oxidation . Besides, a lipid‐lowering effect by downregulating lipogenesis or upregulating fatty acid β‐oxidation was observed in high‐fat diet or alcohol‐fed rodents supplemented with taurine and carnosine . Functional chicken liver hydrolysates containing amounts of BCAAs, taurine and carnosine also demonstrated an ameliorative effect on the development of hepatosteatosis induced by chronic alcohol consumption .…”
Section: Resultsmentioning
confidence: 96%
“…Some amino acids, i.e. histidine, glycine and taurine, have the ability to reduce expression of the pro‐inflammatory transcription factor NF‐κB and downstream cytokine levels . It has been mentioned that glycine lowers the gastric emptying rate of ethanol, resulting in the suppression of ethanol absorption from the gastrointestinal tract; by this means it ameliorates liver damage .…”
Section: Resultsmentioning
confidence: 99%
“…Taurine alleviates liver fat by up‐regulating hepatic lipid oxidation and ameliorating hepatic lipid efflux . Furthermore, taurine improves hepatic inflammation by decreasing proinflammatory cytokines (IL‐1b, IL‐6 and TNF‐a) and diapedesis of lymphocytes in the liver (iNOS and CRP proteins) . Another study reported recently, that taurine might enhance alcohol and fat metabolism, both agents, which might induce liver damage .…”
Section: Discussionmentioning
confidence: 99%